2022
DOI: 10.1038/s41598-021-03599-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of the nodosaurid Struthiosaurus austriacus (Dinosauria: Thyreophora) supports potential ecological differentiations within Ankylosauria

Abstract: Nodosauridae is a group of thyreophoran dinosaurs characterized by a collar of prominent osteoderms. In comparison to its sister group, the often club-tailed ankylosaurids, a different lifestyle of nodosaurids could be assumed based on their neuroanatomy and weaponry, e.g., regarding applied defensive strategies. The holotype of the nodosaurid Struthiosaurus austriacus consists of a single partial braincase from the Late Cretaceous of Austria. Since neuroanatomy is considered to be associated with ecological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Cranial endocasts are used to investigate the neuroanatomy of both extant and extinct vertebrates (e.g., Aristide et al, 2019; Benoit et al, 2017; Beyrand et al, 2019; Iwaniuk et al, 2020; Lautenschlager et al, 2018; Lynch & Allen, 2022; Schade et al, 2022; Weisbecker et al, 2021; Zhu et al, 2020). Virtual endocasts, generated by the increasingly widespread use of computed tomographic scanning, provide the potential to track evolution of brain external morphology through deep time, and the possibility to infer cognitive and sensory abilities, as well as behavior, of taxa (e.g., Balanoff & Bever, 2017; Dozo et al, 2022; Holloway et al, 2009; Jerison, 1973; Neubauer, 2014; Racicot, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cranial endocasts are used to investigate the neuroanatomy of both extant and extinct vertebrates (e.g., Aristide et al, 2019; Benoit et al, 2017; Beyrand et al, 2019; Iwaniuk et al, 2020; Lautenschlager et al, 2018; Lynch & Allen, 2022; Schade et al, 2022; Weisbecker et al, 2021; Zhu et al, 2020). Virtual endocasts, generated by the increasingly widespread use of computed tomographic scanning, provide the potential to track evolution of brain external morphology through deep time, and the possibility to infer cognitive and sensory abilities, as well as behavior, of taxa (e.g., Balanoff & Bever, 2017; Dozo et al, 2022; Holloway et al, 2009; Jerison, 1973; Neubauer, 2014; Racicot, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The unique body plan of ankylosaurs has prompted efforts to infer the functional significance of their bizarre characteristics and reconstruct their palaeobiology. Neuroanatomical studies have revealed an interesting morphological diversity of endocranial structures among ankylosaurs, which suggest an array of different sensory capabilities and behaviours, and that ankylosaurids were more active and socially complex than nodosaurids 5 9 . The ankylosaur appendicular musculoskeletal system was also unique among ornithischians, related to the acquisition of their specific mode of graviportal, quadrupedal posture and locomotion 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…3, 12, 13 ). However, the floccular recess seems not to be a reliable proxy for the size of the actual neural tissue, also containing e.g., vascular tissue 11 , making its potential use problematic 14 . Whereas most sauropod taxa seem not to spot even the slightest floccular recess on the endocast (see e.g.…”
Section: Supplementary Information and Figuresmentioning
confidence: 99%
“…The flocculus is part of the cerebellum and involved in the integration and translation of eye, head and neck movements (VOR, vestibulo-ocular reflex; VCR, vestibulo-collic reflex; see e.g. 11 ). In many previous studies, the floccular recess has been treated as a proxy for the actual cerebellar structure, which induced ecological inferences in fossil taxa (e.g.…”
Section: Supplementary Information and Figuresmentioning
confidence: 99%